Rekonstruksi Makna Al-Qur'an: Studi Kasus Gerakan Kampung Al-Qur'an di Kampung Cijaha Kabupaten Garut - Ahmad, Nurwadjah; Rusmana, Dadan; Kafiyah, Fitroh Ni'matul (Jurnal Penelitian Ilmu Ushuluddin, 2024)
This research aims to examine the results of the meaning of the activities of the Al-Qur'an Village Movement in Cijaha Village, Kadongdong, Subdistrict, Banjarwangi, Garut district, West Java using a typology of meaning from Karl Mannheim's theory of the sociology of knowledge. The activities of the Al-Qur'an village movement are as a forum for students and female students to become mobilizers who serve the community by disseminating knowledge of the Al-Qur'an. This research uses field research with a descriptive-qualitative method based on Karl Mannheim's theory of the sociology of knowledge. Through this research method, findings were produced in the form of the Al-Qur'an Village Movement activities which produced volunteers who were sensitive to social and community conditions who were enthusiastic about practicing the reading and values of the Al-Qur'an, so that it was useful in reducing the illiteracy rate of the Al-Qur'an. deviant social behaviour and personality.